2020
DOI: 10.1002/mabi.202000147
|View full text |Cite
|
Sign up to set email alerts
|

All‐Printed Electronic Skin Based on Deformable and Ionic Mechanotransducer Array

Abstract: Mechanoreceptors in human skin possess high sensitivity, wide sensing range, and high sensing resolution for external stimuli. Several attempts have been made to implement electronic skin (e‐skin) that can mimic human skin. However, previous attempts are limited by the fundamental resolution problem arising from the use of film‐like materials generated through pouring and spinning processes. Here, an all‐printed e‐skin based on deformable ionic mechanotransducer array (IMA) inspired by the physiological tactil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…The inset depicts that the pressure imposed on the ionic-PUA-based sensor not only reduces the thickness of the 80 wt% film between the electrodes but also enables a large number of free ions in the amorphous region of the PUA matrix to migrate to each of the electrode interfaces, thereby resulting in EDL formation with high capacitance. [36,37] As shown in Figure 3d and Figure S4, Supporting Information, we conducted a stability test comprising over 1600 consecutive cycles at 1 V and 1 kHz under various pressure levels (5, 20, and 60 kPa) and confirmed that the capacitance of the sensor with or without pressure remained nearly constant throughout the test, thus indicating reliable and reproducible pressure detection over time. Moreover, we investigated the instant response characteristics of the fabricated pressure sensor against repeated pressure applications.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…The inset depicts that the pressure imposed on the ionic-PUA-based sensor not only reduces the thickness of the 80 wt% film between the electrodes but also enables a large number of free ions in the amorphous region of the PUA matrix to migrate to each of the electrode interfaces, thereby resulting in EDL formation with high capacitance. [36,37] As shown in Figure 3d and Figure S4, Supporting Information, we conducted a stability test comprising over 1600 consecutive cycles at 1 V and 1 kHz under various pressure levels (5, 20, and 60 kPa) and confirmed that the capacitance of the sensor with or without pressure remained nearly constant throughout the test, thus indicating reliable and reproducible pressure detection over time. Moreover, we investigated the instant response characteristics of the fabricated pressure sensor against repeated pressure applications.…”
Section: Resultsmentioning
confidence: 65%
“…Importantly, low-power monolithic ICs as well as a multimodal (showing physical and chemical sensing capabilities) sensor matrix (3 × 3 pressure sensors with thin-film transistor [TFT] array and four chemical sensors) without interference were achieved by designing a photocrosslinked ionic polymer film (ionic polyurethane acrylate [PUA]) including ionic liquids ([EMIM] + [TFSI] − ), a solution-processed amorphous oxide semiconductor (a-InGaZnO), and a protective layer or microhole channel facilitated by a polydimethylsiloxane (PDMS) elastomer film. In particular, this strategy enables a highly reliable piezocapacitive pressure-sensing capability through an electric double layer (EDL) mechanism [36][37][38] at the interface between the ionic polymer film and electrode. Moreover, selective olfactory detection to various chemicals is possible with high sensitivity even under a pressing atmosphere via ion-gas interactions in the chemical sensor matrix.…”
Section: Introductionmentioning
confidence: 99%
“…developing artificial skin. [255] Owing to this, the array integrated process has become an important research direction. Array structure designs can be categorized into planar point and planar cross structures.…”
Section: Artificial Skinmentioning
confidence: 99%
“…Mechanical stimuli can change the distance or the overlapping area between the two electrodes, and the change of distance and area can convert into capacitance change to realize pressure sensing. The acquisition of high sensitivity requires flexible electrode materials and dielectric materials so that even Capacitive Sensors Air chambers into polydimethylsiloxane 0.01-0.03 kPa 0.82 kPa −1 31.2 ms >10 000 [111] All-fibrous multilayer nanostructure 0-135 kPa 0.32 V kPa −1 20 s >10 000 [74] Ionic liquid _ 8.21 kPa −1 8000 [112] MXene/P(VDF-TrFE-CFE) 0.04 to 88.89 kPa 16.0 kPa −1 229 ms ≈1500 [119] PSeD-U <2 kPa 2-10 kPa 0.16 kPa −1 0.03 kPa −1 _ 1000 [164] PVDF/NMP, micro-structured PDMS electrode 0-130 Pa 30.2 kPa −1 at 0.7 Pa 25 s 100 000 [113] Deformable ionic mechanotransducer array _ 2.65 nF kPa −1 47 ms 200 [121] LMs@PDMS 3.87% 0.46 kPa −1 _ _ [120] CB/PDMS 0-0.2 kPa 0.2-1.5 kPa 35 kPa −1 6.6 kPa −1 _ 100 [123] Ag NW/flower/Ag NW 0.6 Pa to 115 kPa 1.54 kPa −1 _ 5000 [165] Piezoresistive sensors MXene@fabric-based Up to 150 kPa 6.31 kPa −1 300 ms 2000 [166] Vertical graphene arrays 2.5 Pa to 1.1 MPa 2.14 kPa − 1 6.7 ms 2000 [138] Zinc oxide nanorod 0-100 kPa 0.095 kPa − 1 140 ms _ [144] Thermoplastic polyurethane/polypyrrole/polydopamine/space fabric 0-10 kPa 97.28 kPa −1 60 ms >500 [167] 3D poly(3,4-ethylenedioxythiophene) coated wrinkled nanofiber film 0-3 kPa 397.54 kPa −1 80 ms 16 500 [168] Graphene oxide self-wrapped Copper nanowire networks 0.1-15 kPa 0.144 kPa −1 150 ms 1000 [169] CNTs-UPy/PUa THF 0-6.1 kPa 8.7 kPa −1 40 ms 10 000 [93] Polyacrylonitrile, cellulose, and MXene 0-50 kPa 179.1 kPa −1 _ 10 000 [136] Carbon black/polyaniline nanoparticles/thermoplastic polyurethane fil 0-680% 0.03% 80 ms 10 000 [47] Serpentine Ti/Au metal traces 1-25 kPa 3.78 kPa −1 200 ms 10 000 [67] MXene nanosheets and Fe 3 O 4 nanoparticles 0-2.5 kPa 5.53 kPa −1 62.2 ms 2500 [41] Poly(vinyl alcohol)/poly(vinylidene fluoride) nanofibers spider web structure 0-135 kPa 0.48 V kPa −1 16 s _ [170] Silicon rubber thin film after Ag NW deposition and PEDOT:PSS coating 0-2 kPa 138.0 kPa −1 128 ms _ [140] Hair-epidermis-dermis aerogel electrode 100 Pa to 30 kPa 137.7 kPa −1 80 ms 10 000 [171] Cellulose/carbon nanotube fiber 0-400 kPa 9.364 kPa −1 <2 ms 10 000…”
Section: Capacitive Tactile Sensorsmentioning
confidence: 99%